Assessment of risk factors associated with hypertension among undergraduate medical students in a medical college in Odisha - Archana Patnaik (Advanced Biomedical Research, 2015)
Background : Hypertension is a non communicable disease of major public health problem resulting increased morbidity and mortality among population. Prehypertension in adolescents and young adults again an important risk factor for developing hypertension in future. So the present study was carried out among medical students with the objectives of (1) to find out the risk factors associated with prehypertension and hypertension, (2) to suggest measures to decrease risk factors. Materials and Methods : It was a cross-sectional study and study duration was from september 2011 to November 2011. The sample size was 200 and the study subjects was selected by systematic random sampling method. A predesigned pretested schedule was used to collect data. Blood pressure (BP) was measured in sitting posture using a standard sphygmomanometer on two different settings and the average was taken for analysis. Results : All the participants were between 18-21 years. Out of 200 study subjects,112 were males and 88 were females. The prehypertension and hypertension percentage was 67% among study subjects. Statistical analysis done was percentage, Chi-square test. Conclusion : Health-care providers should recognize the increased CVD risk of prehypertension and should seek to identify and treat the modifiable risk factors in these persons.